Equilibrium Economics and Business-Cycle Theory - Kuznets, Simon (Quarterly Journal of Economics, 1930)
I. Formulation of the question. A brief historical survey, 381. — II. Recent discussion in Germany: Lederer, Loewe, Carrel, 386. — III. In what sense the equilibrium theory is valid, 392. — IV. The element of time differences: Rosenstein-Rodan, further elaboration, 401. — V. Time differences and the cumulation of random changes, 408. — VI. Summary, 412.